Synthesis, leishmanicidal, trypanocidal and cytotoxic activities of quinoline-chalcone and quinoline-chromone hybrids (2017)
We report herein the synthesis and biological activities (cytotoxicity, leishmanicidal and trypanocidal) of six quinoline-chalcone and five quinoline-chromone hybrids. The synthesized compounds were evaluated against amastigotes forms of L. (V) panamensis which is the most prevalent Leishmania species in Colombia and Trypanosoma cruzi which is the major pathogenic species to humans. Cytotoxicity was evaluated against human U-937 macrophages. Compounds 8-12, 20, 23 and 24 showed activity against L. (V) panamensis while compounds 9, 10, 12, 20 and 23 had activity against T. cruzi with EC50 values lower than 18 mg/Ml. 20 was the most active compound for both L. (V) panamensis and T. cruzi with EC50 of 6.11 ± 0.26 µg/mL (16.91 µM) and 4.09 ± 0.24 (11.32µM), respectively. All hybrids compounds showed better activity than the anti-leishmanial drug meglumine antimoniate. Compounds 20 and 23 showed higher actives than benznidazole, the current antitrypanosomal drug. Although these compounds showed toxicity for mammalian U-937 cells, still have potential to be considered as candidates to antileishmanial or trypanocydal drug development.